2019
DOI: 10.1248/bpb.b19-00056
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Formulation of Sutaehwan Ameliorates Menopausal Anxiety, Depression and Heart Hypertrophy in the VCD-Induced Menopausal Mouse Model

Abstract: Sutaehwan (STH) has been used in Korean medicine for the treatment of abortus habitualis such as fetal restlessness in the uterus. Previously, we reported that a modified formulation of STH, Sutaehwan-Gami, has phytoestrogen-like properties in an ovariectomized menopausal rat model. However, the therapeutic effects of STH and the precise mechanisms by which STH affects various menopausal symptoms remain poorly understood. The current study was designed to explore the effects of a modified form of STH on menopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…First, the brain neurotrophic factor BDNF, described to be multifaceted and considered a flexible hub for synaptic plasticity and cognitive functioning 78 was reduced as a result of APOE4 genotype and VCD treatment. Such observation is in agreement with previous studies focusing on APOE4 79 and VCD treatment separately 80 . Interestingly BDNF is known to influence both mTOR and ERK activation 81 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, the brain neurotrophic factor BDNF, described to be multifaceted and considered a flexible hub for synaptic plasticity and cognitive functioning 78 was reduced as a result of APOE4 genotype and VCD treatment. Such observation is in agreement with previous studies focusing on APOE4 79 and VCD treatment separately 80 . Interestingly BDNF is known to influence both mTOR and ERK activation 81 .…”
Section: Discussionsupporting
confidence: 93%
“…Such observation is in agreement with previous studies focusing on APOE4 79 and VCD treatment separately. 80 Interestingly BDNF is known to influence both mTOR and ERK activation. 81 mTOR signaling was impaired by the APOE4*VCD combination.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens also play a key role in the regulation of calcium homeostasis, and thus fine-tuning the normal process of cardiomyocyte contraction and relaxation [36]. Of course, it has also been suggested that this increased risk is associated with an increase in luteinizing hormone [37] or modulation of T cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…VCD-induced estradiol depletion, unlike OVX, undergoes progressive degeneration like the human menopausal process and residual tissues maintain their secretory function of other hormones [48]. Cognitive impairment, anxiety, and depression were observed in the VCD-induced estradiol depletion model [37,49]. Based on the literature, the optimal dose of VCD to accelerate estradiol depletion was 160 mg/kg for 20 days [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Radix Polygalae (RP) is the root of Polygala tenuifolia Willdenow and has traditionally been used as an expectorant, tranquilizer, and memory booster [34][35][36]. Recent studies have demonstrated that it may have effects on dementia prevention, neuroprotection, and antidepressant [37]. RP improved memory and increased ChAT activity in β-amyloid induced learning and memory-impaired animal models [38].…”
Section: Introductionmentioning
confidence: 99%